2022
DOI: 10.1002/ldr.4254
|View full text |Cite
|
Sign up to set email alerts
|

Leaf nutrient resorption differs among canopy and understory plant species in subtropical Eucalyptus and Acacia plantations

Abstract: Although plants are known to conserve nutrients by resorbing them from senescing leaves, how resorption of foliar macro‐ and micronutrients is affected by plant growth form (e.g., trees, shrubs, and ferns) and forest age are not well understood. The current study was conducted in four subtropical monoculture plantations: Eucalyptus and Acacia plantations in 14 and 35 years old, respectively. Leaf resorption efficiencies (REs) and resorption proficiencies (RPs) of nitrogen (N), phosphorus (P), potassium (K), ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
(154 reference statements)
2
4
0
Order By: Relevance
“…This nding seemed to be in accordance with earlier studies (Deng et al 2019;Wang et al 2022a). In addition, NRE was closely related to soil K for the RG, indicating that soil nutrients might be served as an indicator of nutrient resorption e ciencies in the soil and water conservation site.…”
Section: Response Of Nutrient Homeostasis and Nutrient Utilization St...supporting
confidence: 94%
See 2 more Smart Citations
“…This nding seemed to be in accordance with earlier studies (Deng et al 2019;Wang et al 2022a). In addition, NRE was closely related to soil K for the RG, indicating that soil nutrients might be served as an indicator of nutrient resorption e ciencies in the soil and water conservation site.…”
Section: Response Of Nutrient Homeostasis and Nutrient Utilization St...supporting
confidence: 94%
“…Previous studies have found that the plants have higher nutrient resorption e ciencies in the fertile soil than in the unfertile soil (Drenovsky et al 2013;Xu et al 2020). In addition, the forest stands profoundly regulate the nutrient resorption (Chen and Chen 2021; Wang et al 2022a). Leaf and litter nutrients status also impact the plants nutrient resorption, but results vary among different studies (Hattenschwiler et al 2008 Age and population density may alter carbon and nutrient stock for the tea plantation (Kamau et al 2008), and environments also can affect nutrient cycling in tea plantation (Hu et al 2019).…”
Section: ; Seidel Et Al 2022)mentioning
confidence: 99%
See 1 more Smart Citation
“…At the global scale, N and P resorption increases as their availability in soil decrease (Yuan & Chen, 2015). However, at local scales, the relationship between P resorption and soil P availability is not consistent, with decreased, non‐responsive, or even increased P resorption as soil P availability increases (See et al ., 2015; Wang et al ., 2022; Zhang et al ., 2022). There is a general tradeoff between P resorption and organic P mineralization (Deng et al ., 2018), as high P resorption decreases P concentration in the litter and thus reduces the substrate quality for soil microbes.…”
Section: Introductionmentioning
confidence: 99%
“…It helps to characterize nutrient allocation and strategies under environmental changes (Milla et al, 2005). Nutrient resorption refers to the uptake of nutrients from senesced leaves and nutrient allocation and utilization of those nutrients (Chen et al, 2021a;Wang et al, 2022). Previous studies have found that P and K resorption efficiencies are significantly higher than N resorption efficiency in the nutrient-poor soils of a tropical forest (Urbina et al, 2021).…”
Section: Introductionmentioning
confidence: 99%